Multi-parenthood and contemporary family forms in French studies - Agnès Martial (Antropologia, 2019)
Analysing the case of France, this article presents a reflection on the notion of multi-parenthood in the study of contemporary family models – adopted families, stepfamilies, donor-conceived families in the context of ART. It retraces the recent use of the notion in French kinship and family studies and its different interpretations in scientific or political debates. The article then examines multi-parental models and the issues they face at three moments of family life: conception and birth, childhood and education, cross-generational transmission. In these families, additional figures and relationships seem to be uncertain and fragile, in particular when they are restricted to the sole procreative dimension, while choice and experience are increasingly valued – leading in some cases to the legal recognition of a third bond of kinship. Thus multi-parental situations lead us to reconsider the value of blood, flesh or even genes in contemporary understandings of kinship.